Nano-mechanical investigation of engineered bone tissue and of the osteochondral interface. (2019) - Boi, M.; Marchiori, G.; Berni, M.; Fini, M.; Russo, A.; Bianchi, M.
Abstract: Nanoindentation has been emerging as a powerful tool for the investigation of the quality of bone tissue, as it allows to relate compositional/structural heterogeneity to mechanical variations at the micro- and nano-scale. To date, the investigation of nanomechanical properties of bone has been almost exclusively limited to healthy or pathologic tissues, while very few studies attempted to evaluate the mechanical properties of the tissue during the regeneration process. Here, we report the analysis by nanoindentation of the mechanical properties of healing tissue considering different animal models (rabbit and sheep), anatomical regions (condylar osteochondral interface and femoral trabecular bone), comparing pre-existent (i.e. native) and newly-formed (i.e. engineered) tissue according to different engineering approaches. In particular, we focused on bone tissue regenerated by means of nanostructured multi-layered biomimetic scaffolds or macroporous hydroxyapatite scaffolds implanted in critical-size bone defects. Our data confirm that nanoindentation represents an extremely useful tool to follow the degree of maturation of bone tissue during the healing process, for instance allowing the comparison of the efficacy of different regenerative approaches. In addition, the knowledge of the level of reconstruction of the osteochondral interface by revealing the (nano-)mechanical gradient can provide clinically relevant information to predict the correct load transfer from the cartilage to the underlying bone tissue